Note on Lie Point Symmetries of Burgers Equations - Freire, I. L. (Trends in Computational and Applied Mathematics, 2010)
Abstract. In this note we study the Lie point symmetries of a class of evolution equations and obtain a group classification of these equations. We also identify the classical Lie algebras that the symmetry Lie algebras are isomorphic to.